BSCI-10. NEUROLOGICAL DYSFUNCTION CAUSED BY BRAIN TUMOR-GENERATED SOLID STRESS IS REVERSED BY LITHIUM. (12th August 2019) - Seano, Giorgio; Nia, Hadi; Emblem, Kyrre; Datta, Meenal; Ren, Jun; Kloepper, Jonas; Krishnan, Shanmugarajan; Ghosh, Mitrajit; Pinho, Marco; Askoxylakis, Vasileios; Ferraro, Gino; Riedemann, Lars; et al.
Abstract: The compression of brain tissue by a tumor mass is believed to be a major cause of the clinical symptoms seen in patients. However, the biological consequences of these physical stresses on the brain tissue are unknown. Using clinical imaging and preclinical studies, we discovered that a subgroup of primary and metastatic brain tumors, classified as nodular based on the growth pattern, exert compressive solid stress on the surrounding brain tissue, leading to a decrease in local vascular perfusion, as well as neuronal death and impaired function. We demonstrated a causal link between solid stress and neurological dysfunction, by applying and removing cerebral compression, mimicking the mechanics of tumor growth and surgical resection respectively. Finally, we showed that treatment with lithium reduced solid stress-induced neuronal death and improved motor coordination in mice. Our results indicate that brain tumor-generated solid stress impairs neurological function in patients and show lithium as a potential therapeutic intervention to counter these effects.